National and cultural specificity of stable expressions with the zoonymic component “wolf” in English and Kazakh languages - Alshynbayeva, M.A.; Veselinov, D. (KU Publ., 2021)
The article focuses on a linguocultural analysis of English and Kazakh stable expressions nominating the image of a wolf. The aim is to study stable expressions through the prism of the values of the linguocultural community, in particular, English and Kazakh, represented in it. In the course of the analysis groups of stable expressions were identified and their differences and similarities in the compared languages were examined, as well as their national and cultural specificity, based on the action of universal cultural codes, was revealed. The national-cultural specificity of zoonyms is determined by a number of extralinguistic factors: the location of the country, the living conditions of the people, their customs and traditions, history, religion and sociopolitical structure. All this fixes national-specific connotations for zoonyms and determines their productivity. The practical significance of the research lies in the possibility of using its results in teaching, first of all, the theory of language, English and Kazakh phraseology, special courses in cultural linguistics, sociolinguistics, and intercultural communication. Further, research of phraseological units with a zoonym component can be carried out on the basis of the inclusion of other distant languages, for example, German, which will reveal universal features in the perception of animals from the perspective of a three-sided analysis.
Ағылшын жəне қазақ тілдеріндегі «қасқыр» зоонимикалық компоненті бар тұрақты тіркестердің ұлттық-мəдени ерекшелігі
Национально-культурная специфика устойчивых выражений с зоонимичным компонентом «волк» в английском и казахском языках
Keywords: language; phraseology; wolf; English language; Kazakh language